Stakeholders - Egan, John (Henry Stewart Talks, 2012)
Definition & History of stakeholders, Communications & Relationship marketing theory, Stakeholder theory, classification, management issues & mapping, The importance of classification and its weaknesses, Stakeholder groups, Urgency, legitimacy and power, Primary and voluntary & social stakeholders, Contractual & community stakeholders, Stakeholders exchange & communication, Stakeholder analysis & audit, Power to influence